Identifying heavy metal levels in historical flood water deposits using sediment cores. (15th November 2016) - Lintern, Anna; Leahy, Paul J.; Heijnis, Henk; Zawadzki, Atun; Gadd, Patricia; Jacobsen, Geraldine; Deletic, Ana; Mccarthy, David T.
Abstract: When designing mitigation and restoration strategies for aquatic systems affected by heavy metal contamination, we must first understand the sources of these pollutants. In this study, we introduce a methodology that identifies the heavy metal levels in floodplain lake sediments deposited by one source; fluvial floods. This is done by comparing sediment core heavy metal profiles (i.e., historical pollution trends) to physical and chemical properties of sediments in these cores (i.e., historical flooding trends). This methodology is applied to Willsmere and Bolin Billabongs, two urban floodplain lakes (billabongs) of the Yarra River (South-East Australia). Both billabongs are periodically inundated by flooding of the Yarra River and one billabong (Willsmere Billabong) is connected to an urban stormwater drainage network. 1–2-m long sediment cores (containing sediment deposits up to 500 years old) were taken from the billabongs and analysed for heavy metal concentrations (arsenic, chromium, copper, lead, nickel, zinc). In cores from both billabongs, arsenic concentrations are high in the flood-borne sediments. In Bolin Billabong, absolute metal levels are similar in flood and non-flood deposits. In Willsmere Billabong, absolute copper, lead and zinc levels were generally lower in fluvial flood-borne sediments in the core compared to non-fluvial sediments. This suggests that heavy metal concentrations in Bolin Billabong sediments are relatively similar regardless of whether or not fluvial flooding is occurring. However for Willsmere Billabong, heavy metal concentrations are high when overland runoff, direct urban stormwater discharges or atmospheric deposition is occurring. As such, reducing the heavy metal concentrations in these transport pathways will be of great importance when trying to reduce heavy metal concentrations in Willsmere Billabong sediments. This study presents a proof-of-concept that can be applied to other polluted aquatic systems, to understand the importance of river floods in the contamination of the bed sediments of aquatic systems. As a cost effective and less time consuming alternative to extensive field monitoring, our proposed method can be used to identify the key sources of pollution and therefore support the development of effective management strategies. Graphical abstract: Highlights: Bed sediment cores can show long-term trends in pollution of aquatic systems. These trends can be used to understand heavy metal levels in flood deposits. Stormwater deposits had higher metal concentrations than river flood deposits. This approach could be used to help develop pollution mitigation strategies.